Evaluación de la eficiencia productiva del cultivo de la vid en la región Piura 2018 – 2023 - Castillo Sandoval , Omar (2024)
The objective of this study is to evaluate the productive efficiency of grape cultivation in the Piura region, during the period between 2017 and 2022. To do this, a non-experimental research design will be used, in which data will be collected secondary from various sources. The data will be analyzed statistically to determine the influence of the productive efficiency of grape cultivation in the Piura region. The results of the study show that the productive efficiency of grape cultivation in the Piura region has improved significantly during the study period. Grape yields have increased by an average of 10%, production costs have decreased by an average of 5%, and water efficiency has improved by an average of 20%.